Pengaruh Model Pembelajaran Mind Mapping dan Contextual Teaching Learning Terhadap HOTS Siswa Kelas V Sekolah Dadar - Joanna, Ingke; Setyawan, Agung (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2023)
This study aims to examine the effect of mind mapping and contextual teaching-learning models on HOTS fifth-grade students and measure the effectiveness of fifth-grade student learning before and after being given treatment. This research was conducted at SDN Gedongombo 3, 4, and 5 in Tuban Regency on thematic theme 9, sub-theme 1. This research was a quasi-experimental study with a pretest-posttest control group design. The sampling technique was purposive sampling involving fifth-grade students at SDN Gedongombo 1, 2, 3, 4, 5. The data collection technique was carried out using tests, questionnaires, observation, documentation, and hypothesis testing using simple linear regression. Based on the results of the linear regression calculation, the sig(2-tailed) value was 0.036 <0.05 and the ttest value was 2.202 > ttable 2.048 in the experimental group 1 and the sig(2-tailed) value was 0.001 <0.05 and the ttest value was 6.357> ttable 2.035 in experimental group 2 so that it shows that the mind mapping and contextual teaching- learning models have an effect on the HOTS of fifth-grade students at SDN Gedongombo 4 and 5. The effect size test results of the mind mapping model are 2.21116 and the contextual teaching-learning model is 2.14928 which is the second These results include the category of strong effects.